Kondisi Terumbu Karang dan Biota Lainnya di Perairan Kecamatan Selat Nasik Kabupaten Belitung Tahun 2007-2008 - Sjafrie, Nurul D. M. (Jurnal Perikanan Universitas Gadjah Mada, 2009)
The aims of  this study was to monitor the coral reef condition, coral fishes and benthic organisms in Selat Nasik Sub District waters. The sampling  was carried out on March 2008 in 12 stations at Selat Nasik waters that were similar to sampling station for 2007 study. Observations on benthic lifeform was done using  LIT (line intercept transect), coral fishes was observed using Underwater Visual Census (UVC) whereas benthic organisms was counted  using Belt Transect. The result  showed that  the coral reef condition in Selat Nasik Sub District water’s was still in good condition. Coral Fishes increased in number, especially target fishes and indicator fishes. Bentic organisms such as Diadema and Fungia increased in number, whereas Tridacna decreased as well.